(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This scientific article explores the role and significance of national games in the training and education of football goalkeepers. The study analyzes methods for developing the technical and tactical skills of goalkeepers through national games. In the experimental group, football players participated in exercises based on national games, and their reaction time, effectiveness in blocking shots, and accuracy in targeting were measured. The results demonstrated that national games serve as an effective tool in improving goalkeepers’ technical and psychological skills, contributing to the enhancement of their physical and mental well-being.